The Status Quo of Sustainable Tourism Development in Phuket. A Qualitative Assessment - FUCHS, Kevin; SINCHAROENKUL, Kris (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
Sustainable tourism is an increasingly fashionable term that is strongly correlated with the global age of increased mobility. While there is increasing interest in sustainable tourism, there is no contemporary research that describes the current state of Phuket, Thailand, the mass-tourism destination. An in-depth review of existing literature revealed that sustainable tourism at large receives a great deal of attention in its current state. This paper aimed to go beyond the common theme of sustainable tourism and conducted a thorough analysis about the status quo in Phuket with regard to sustainable tourism. Qualitative data was collected through semi-structured interviews (n=5) with industry experts and later analyzed the content by the means of thematic analysis. The research is specific to Phuket; therefore, the results of this research are not generalizable to other mass-tourism locations. There is no one-size-fits-all solution, but it is evident that stakeholders in Phuket recognize the importance of sustainable tourism. Moreover, the lack of accountability, coherent leadership, and consistency resulted in a high failure rate when initiatives were launched to improve sustainable tourism behavior in Phuket.